Sensitivity assessment of sea lice to chemotherapeutants: Current bioassays and best practices. Issue 6 (18th December 2017) - Marín, S L; Mancilla, J; Hausdorf, M A; Bouchard, D; Tudor, M S; Kane, F
Abstract: Traditional bioassays are still necessary to test sensitivity of sea lice species to chemotherapeutants, but the methodology applied by the different scientists has varied over time in respect to that proposed in "Sea lice resistance to chemotherapeutants: A handbook in resistance management" (2006). These divergences motivated the organization of a workshop during the Sea Lice 2016 conference "Standardization of traditional bioassay process by sharing best practices." There was an agreement by the attendants to update the handbook. The objective of this article is to provide a baseline analysis of the methodology for traditional bioassays and to identify procedures that need to be addressed to standardize the protocol. The methodology was divided into the following steps: bioassay design; material and equipment; sea lice collection, transportation and laboratory reception; preparation of dilution; parasite exposure; response evaluation; data analysis; and reporting. Information from the presentations of the workshop, and also from other studies, allowed for the identification of procedures inside a given step that need to be standardized as they were reported to be performed differently by the different working groups. Bioassay design and response evaluation were the targeted steps where more procedures need to be analysed and agreed upon.